STUDY ANALYSIS OF DRAINAGE ROAD ADAM MALIK CITY SAMARINDA. - SETIAWAN, AGUS (KURVA S JURNAL MAHASISWA, 2018)
Agus Setiawan, NPM 11.11.1001.7311.092, 2011, Civil Engineering Study Program, Faculty of Engineering, University of 17 August 1945 Samarinda. Flood is natural disaster that occurs due to the inability of channel of a region to accommodate the high rainfall in the region. One solution to overcome the flood is to improve the dimensions of the drainage channel to be able to accommodate the amount of water debit contained in a region. This research took place in Streat Adam Malik, Kec. Sungai Kunjang, Samarinda City. Calculation analysis using Gumbel and Log Person Type III method to calculate drainage channel capacity. Based on the calculation of the existing flood discharge of drainage channel at the research location that is smallest 2,571 m3/dt - biggest 3,450 m3/dt and flood discharge design at Streat Adam Malik Samarinda City that is smallest 3.114 m3/dt - biggest 4,490 m3/dt with kala 10 years until year 2027. With the design of dimensional cross-sectional capacity : an average upper width of 2.00 meters width an average of 2,00 meters, and an average height of 1,50 meters. From the calculation results can be concluded that the drainage channel capacity enough to accommodate all the water discharge that exist in the area.